Dangdut Koplo: Memahami Perkembangan hingga Pelarangan - Raditya, Michael H.B. (Studi Budaya Nusantara, 2017)
ABSTRACT Nowadays, Dangdut Koplo has become a mass product, which commodified by industry music of Indonesia. Was born in the northern coast of Java -Pantura-, Dangdut Koplo has develop since Dangdut Television become popular. In 2003, Inul phenomenon was replacing Dangdut star whose fame at the time, such as: Rhoma Irama. But Rhoma and colleagues didn't accept that, and try to ban Inul and Dangdut Koplo in Dangdut Industry.Â It is undeniable that Dangdut Koplo developed by ban process. Rhoma Irama and Many Groups who has a corelation with religion tried to ban Dangdut Koplo, and Inul. But the commodification's power worked, Inul and singers from Pantura more popular. In 2016, KPI do the ban Dangdut Koplo. Thirteen songs Dangdut Koplo blocked. Regarding from these thing, this article will discuss about existance of Dangdut Koplo, about developing and barriers. And this article isn't support group who confronted each other, this article who i wrote it, is trying to articulate about essence that contained on Dangdut Koplo. The result of this article is an alternative point of view's to face the problem in holistic way.